2009
DOI: 10.1088/0953-2048/23/1/014009
|View full text |Cite
|
Sign up to set email alerts
|

Neutron irradiation of coated conductors

Abstract: Various commercial coated conductors were irradiated with fast neutrons in order to introduce randomly distributed, uncorrelated defects which increase the critical current density, J c , in a wide temperature and field range. The J c -anisotropy is significantly reduced and the angular dependence of J c does not obey the anisotropic scaling approach. These defects enhance the irreversibility line in not fully optimized tapes, but they do not in state-of-the-art conductors. Neutron irradiation provides a clear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 26 publications
(43 reference statements)
5
38
1
3
Order By: Relevance
“…An improvement in flux pinning was seen in proton irradiated sintered ceramic pellets of YBCO and Bi2Sr2Ca2Cu3O10 by Mezzetti et al [74], and in ion irradiated melt-textured YBCO with a high concentration of discontinuous columnar defects by Fuchs et al [75]. However, Behera et al [76] found that swift heavy ion irradiation of YBCO granular thick films damaged grain boundaries, and Eisterer et al [77] found that neutron irradiation of YBCO coated conductors found no improvements. Irradiation is a promising route but the parameter space is vast and systematic studies with good information about values of DN and PN will be required to optimise c .…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in flux pinning was seen in proton irradiated sintered ceramic pellets of YBCO and Bi2Sr2Ca2Cu3O10 by Mezzetti et al [74], and in ion irradiated melt-textured YBCO with a high concentration of discontinuous columnar defects by Fuchs et al [75]. However, Behera et al [76] found that swift heavy ion irradiation of YBCO granular thick films damaged grain boundaries, and Eisterer et al [77] found that neutron irradiation of YBCO coated conductors found no improvements. Irradiation is a promising route but the parameter space is vast and systematic studies with good information about values of DN and PN will be required to optimise c .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we could also mention the use of neutron irradiation as a tool to distinguish between all types of CCs among the low field regions where granularity effects are dominant from high magnetic fields where vortex pinning is enhanced by the created defects. Of course, understanding these issues is essential in order to use these materials in magnets for fusion applications [87].…”
Section: Vortex Pinning Strategiesmentioning
confidence: 99%
“…В-третьих, ВТСП-ленты термоядерных устройств должны быть устойчивы к нейтронной радиации. Эффективное сечение поглощения медленных нейтронов изотопами 155 Gd и 157 Gd на пять порядков выше (~2,510 5 барн у 157 Gd), а у 156 Gd, 158 Gd и 160 Gd примерно такое же, как у иттрия, -порядка 1 барн [11]. При захвате нейтрона происходит ядерная реакция, например, 157 Gd + n → 158 Gd + γ с выделением энергии в слое ВТСП порядка 30 кэВ, что приводит к разрушению ВТСП в объёме нескольких элементарных ячеек [12].…”
Section: требования к втсп-лентам для тнэ токамаковunclassified